Entre o relato e o ato: concepções de oralidade em relatos de professores do 1° ano do ensino fundamental participantes do PNAIC - Lima, Maria Sonaly Machado de (2020)
The theoretical-investigative scenario still lacks research focused on the debate on the place of orality in the school teaching-learning process, in particular, in the literacy cycle, as well as on the specificities of orality as a teaching object and / or axis of Portuguese language teaching. In this context, this research directed its investigative course from the questioning which conceptions of orality emerge from the teaching practices of teachers of the 1st year of elementary school, participants in the “Pacto Nacional pela Alfabetização na Idade Certa (PNAIC)”. This way, we seek to focus on the discussion about the teaching of orality in Basic Education and, with a quantitative-qualitative study, we have as a general objective to reflect on the orality concepts that materialize in the teaching practices of literacy teachers participating in the PNAIC-PB. Theoretically, this study is based on Bakhtin (2000; 2006), that supports it with the interactionist theory of language; Vygotsky (1991; 2005), that brings the relevance of social and historical-cultural factors in the development of language; Schneuwly e Dolz (2004), Marcuschi (2001; 2008) e Zumthor (1993), among others, that supports the discussion on oralities. Based on the proposed objectives, methodologically, we analyzed experience reports teachers who work in the first year of Elementary School, participants in the continuing education program of the PNAIC. From these reports, which describe practices with orality, we seek to understand, through the materiality of the actions reported, the theoretical concepts that support them in the classroom. This investigative course revealed that the teachers had the explicit intention to carry out a Sociointeractionist teaching practice and we believe that these intentions were the result of a continuous training in service. However, it was demonstrated that this training, regarding to the specificities of the oral, it was still not enough to support them in the theoretical and methodological aspects of language teaching. What was evident in the teaching practices reported were hybrid methodologies that, in general, tended towards an interactive approach to language.